PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA BANK UMUM MILIK PEMERINTAH - Ida Ayu Agung Idawati; I Gede Surya Pratama; IA Cynthia Saisaria Mandasari (UNHI Press, 2018)
One of the considerations of investors in investing in shares is fluctuations in stock prices. Stock prices are one indicator of the success of company management. Investor or prospective investor trust is very beneficial for the issuer, because the more people who trust the issuer, the stronger the desire to invest in the issuer. The purpose of this study was to determine the financial performance as measured by the variable Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), Loan to Deposit Ratio (LDR) and Return On Equity (ROE) to the stock prices of government-owned commercial banks on the IDX. The technical analysis used in this study is multiple linear regression and t (t-test) for partial analysis. Based on the results of multiple linear regression analysis, the regression equation Y = 18.905 + 0.149 (X1) +0.393 (X2) -0.487 (X3) + 0.238 (X4) is obtained. T-test testing from the regression results obtained that the Capital Adequacy Ratio and Return On Equity partially did not have a significant effect on stock prices. While the Net Profit Margin and Loan to Deposit Ratio partially have a significant effect on stock prices.